Synbiotic Soygurt Tempe Extract as A Functional Drink for Stunting Prevention - Mellia Silvy Irdianty; Agnes Sri Harti; Erlina Windyastuti (International Journal of Public Health Excellence (IJPHE), 2023)
Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time due to the provision of food that does not meet nutritional needs. Toddlers with stunting are a chronic nutritional problem which can be caused by many factors, socioeconomic conditions, maternal nutrition during pregnancy, illness in infants, and lack of nutritional intake in infants. Synbiotics (prebiotics and probiotics) as an effective alternative for stunting Analyzing the effectiveness of prebiotic tempeh soyghurt as a functional drink for stunting prevention. The research method is an experimental research including fermenting prebiotic tempeh and prebiotic tempe extract, making prebiotic tempeh soygurt, and analyzing the nutritional content and product quality of probiotic tempeh soygurt referring to SNI 7552:2009 concerning flavored fermented milk including chemical physics analysis, namely the hedonic method organoleptic test, pH, acidity, protein, fat, ash content, fiber, water content and microbiological tests, namely MPN coliform and Salmonella sp. Data analysis used bivariate and multivariate Anova tests. Organoleptic test results for prebiotic soygurt extract of tempeh product with the addition of chitosan (0.5%; 1.0%; 1.5%; 2.0%) using lactic acid bacteria (LAB) inoculum in the rather dislike category (value 3.00) to rather like (value 4.50) . Physical test results showed liquid texture, yellowish color, aroma of tempeh extract, sour taste. Chemical test results (w/b) fat content 3.34%; milk solids 13.19%, non-fat milk solids 9.25%; proteins 0.69%; ash content 0.19%, acidity 0.69% and sugar content 0.59%. Microbiological tests showed MPN coliform <3 cells/100 ml sample and Salmonella sp/25 ml negative results. CONCLUSION: Soygurt extract tempe prebiotic product meets the physical, chemical and microbiological requirements so that it can function as a functional drink for stunting prevention can be concluded that the accuracy of measuring body weight depends on gender.